EFEKTIVITAS GEL EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH YANG DIINFEKSI Staphylococcus aureus - riski dwi utami; olvaria misfa; alfiza rahmanita; mahendra (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
The World Health Organization (WHO) estimates that around 180,000 deaths occur due to burns. The healing process of burn wounds is influenced by several factors, such as the area, depth of the burn and infection. One of the bacteria that causes infection in burn wounds is Staphylococcus aureus. Starfruit leaf extract, used in gel form, is a natural remedy that offers benefits for burn treatment. This study aimed to analyze the effectiveness of starfruit leaf extract gel in healing burn wounds infected with Staphylococcus aureus in white rats. This research method was true experimental with a randomized posttest only control group design with 20 rats divided into four groups, namely the positive control group using bioplacenton (C1), the negative control group using gel base (C2), treatment group 1 with starfruit leaf extract gel with a concentration of 6% (P1) and group treatment 2 with starfruit leaf extract gel with a concentration of 12% (P2). The study found the smallest burn area on day 3 and day 7 was group C1 with an average of 2,799 cm2 and 2,324 cm2. On the 14th day it was group P2 with an average of 1,134 cm2. On the 21st day it was groups C1 and P2 with a mean of 0.163 cm2 and 0.164 cm2. The One-Way Anova test revealed significant differences in burn wound healing on days 3, 7, 14, and 21 (p < 0.05). Starfruit leaf extract gel effectively heals burns in white mice infected with S. aureus, with 12% concentration